Teori Makna dalam Struktur Linguistik Arab Perspektif Mufasir Masa Klasik - Ahmad Atabik (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2020)
This article aims to examine the theory of meaning in the structure of Arabic linguistics that is studied by classical era commentators. In the classical era, the study that became a concentration of the study of al-Qur'an is the understanding of the meaning of the Qur'an with an Arabic linguistic approach. To get the ideal meaning from the verses of the Koran they pay attention to i’rab (Arabic grammar). They are concerned in the field of language criticism through grammatical, stylistic, and semantic approaches. Theories of meaning in classical times are supported by various works of classical Arabic linguists entitled Ma‘ānī al-Qur’ān, al-Farrā ’, al-Kisā’ī, al-Zajjāj, and al-Naḥḥās. These works are very significant in the development of the theorization of meaning from the point of view of the structure of the building (grammatical language). The theory of meaning is also supported by the study of stylistics (language style /uslūb). The study of the stylistic al-Qur'an in the theory of meaning is strengthened by al-Jā hiz and al-Jurjānī in their respective works. The final meaning theory can be found in the Qur'anic semantic studies. This study is considered as an ideal method in exposing the meaning of the Qur'anic language. Semantic studies of al-Qur'an are supported by the theory of al-wujūh wa al-naẓāir and siyāq (the context of the meaning of language). The study of the Wujūh and Naẓāir is a method of understanding the message of meaning which is possessed by the verses of the Qur'an, once studied by Ibn al-Jauzī. While siyāq is an indicator used in determining the meaning desired by mutakallim, it has been studied by Ibn Daqīq al-‘Id.